Lung cancer mortality and municipal marginalization in Mexico, 1998-2016 - Laura Alejandra Ramírez-Tirado; Cesar Enrique Uribe-Ortíz; Oscar Arrieta; Laura L Tirado-Gómez (Instituto Nacional de Salud Pública, 2019)
Objective. To analyze the mortality trend of lung cancer (LC) in Mexico, according to the municipality marginalization index (MMI) by age group and sex, during the period 1998-2016. Materials and methods. The information on mortality, population and MMI was obtained from the National Institute of Statistics and Geography (INEGI) and the National Council of Population (Conapo). The adjusted LC mortality rate trends were analyzed using the joinpoint regression analysis. A total of 126 132 deaths were included. Results. The adjusted LC mortality rate decreased from 7.83 to 4.97 100 000 inhabitants during the period from 1998-2016, but the decrease was found to be less in women and in areas with very high marginalization. Conclusions. Unequal reduction in LC mortality according to the degree of marginalization are related to early diagnosis, timely treatment and inequity in medical services. This inequity affects mainly the populations of women, highly marginalized groups and older populations.